Characterization of Lapindo Mud-Based Nanocatalyst and Quality Testing of Biodiesel from Used Cooking Oil via Transesterification Reaction - Taqiya, Rufaidah Zulfa; Samik, Samik (Indonesian Journal of Chemical Research, 2025)
This study explores the transesterification of used cooking oil using a Lapindo mud-based nanocatalyst and evaluates the resulting biodiesel quality. The reaction was carried out via the reflux method for 2 hours at 65°C, with a methanol-to-oil molar ratio of 9:1 and a catalyst-to-oil weight ratio of 3:100. The high SiO₂ metal oxide content in Lapindo mud functions as a heterogeneous catalyst. Nanocatalyst synthesis involved calcination followed by ball milling. Characterization confirmed the presence of SiO₂: FTIR analysis identified Si-O-Si functional groups at 1168 cm⁻¹, XRD revealed SiO₂ crystals at 2θ values of 20.18°, 26.68°, 42.40°, and others, while XRF showed 47.0% SiO₂ content. PSA results indicated a particle size distribution of 514.3 ± 361.8 nm. Biodiesel analysis using GC-MS showed a methyl ester content of 99.26%. Other quality parameters included density (929.4 kg/m³), viscosity (4.52 mm²/s), water content (0.097%), and acid number (0.50 mg-KOH/g). These findings suggest that the Lapindo mud-based nanocatalyst is highly effective in promoting transesterification and presents a promising, eco-friendly alternative for biodiesel production from used cooking oil.